Response Khan S P Khan, et al. (J Pak Med Assoc. 74: 1654-1658, September 2024) Role of oral hypoglycaemic drugs in preventing complication in non-alcoholic fatty liver disease with type 2 diabetes mellitus - Museera Zahid; Samia Perwaiz Khan; Sana Ershad; Safia Izhar; Rizwana Warraich; Ali Asgha (Journal of the Pakistan Medical Association, 2025)
Thank you for your comments on our paper. As we havementioned in our article the initial total sample size ofparticipants in this study diagnosed with NAFLD byperforming ultrasound liver was 200, out of total numberof these 154 were diagnosed as NAFLD and T2DM and 46with fatty liver changes only. Thus, showing a high level ofassociation of NAFLD with TY2DM. They were dividedinto four treatment groups. Post-treatment improvementwas reported in forty eight patients, participants of GroupA on (Empagliflozin + metformin) twenty (42%) improved,by reduced HBA1c levels, BMI and SGPT/SGOT levelsalong with improvement in fatty liver changes. We doacknowledge that small sample size in follow-up being alimitation of our study. Larger Studies are the need of theday and also our intention. Continued...